Outcome of Complicated Groin Hernia Repair at B.P. Koirala Institute of Health Sciences: A Retrospective Study - Joshi, Brikh Raj; Gautam, Swotantra; Sah, Suresh; Poudel, Nabin; Thapa, Prashrit (Birat Journal of Health Sciences, 2018)
Introduction: Groin hernias are common problem worldwide with approximate incidence of 5%. Indirect inguinal hernia is the commonest hernia irrespective of gender. The prevalence as well as complication of inguinal hernia will increase with increasing age. Strangulation, the most common serious complication of inguinal hernia occurs in 1 to 3 % of the patients. Outcome of the treatment depends on the duration of presentation, co-morbidities and extent of the surgery. Objective: The objectives were to study the different clinical presentation, surgical options and outcome of complicated groin hernia in tertiary care centre. Methodology: This retrospective review of case sheet was conducted in the department of surgery. We reviewed the record file of complicated groin hernia patients, irrespective of age and gender from January 2008 to December 2016 (8 years). Ethical Clearance was obtained from institutional review committee. Statistical analysis was performed using SPSS for windows, version 11.5(SPSS Inc.,Chicago,IL). The data were presented in percentage, mean and standard deviation. Results Out of 45 patients, majority were male 37(82.2%) and commonly effected age group was more than 60 years 18(40%) followed by infants and adolescents. Majorities had complicated inguinal hernias 42 (93.3%) followed by femoral hernia, i.e. 3(7%). Majority of patient underwent inguino-scrotal exploration 26(57.77%) followed by herniotomy 9(20%) and hernioplasty 7(15.55%). Most of the patients were discharged from the hospital 37(82.2%). Conclusion: Most common type of complicated hernia is inguinal hernia; irreducibility and pain were commonest symptoms at presentation. Commonly performed operation is inguinoscrotal exploration and herniorraphy with good surgical outcome. BJHS 2018;3(2)6:395-398.